2012
DOI: 10.1007/s11033-012-1752-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of STAT4 gene single-nucleotide polymorphism to systemic lupus erythematosus in the Polish population

Abstract: The STAT4 has been found to be a susceptible gene in the development of systemic lupus erythematosus (SLE) in various populations. There are evident population differences in the context of clinical manifestations of SLE, therefore we investigated the prevalence of the STAT4 G > C (rs7582694) polymorphism in patients with SLE (n = 253) and controls (n = 521) in a sample of the Polish population. We found that patients with the STAT4 C/G and CC genotypes exhibited a 1.583-fold increased risk of SLE incidence (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…STAT4 SNPs (rs7574865, rs7582694) were determined by the polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) method [22], [23]. The primers used for the PCR reaction were rs7574865, F:5′-AAAGAAGTGGGATAAAAAGAAGTTTG-3′, R:5′-CCACTGAAATAAGATAACCACTGT-3′, and rs7582694, F:5′-ATCCAACTCTTCTCAGCCCTT-3′, R:5′-TCATAATCAGGAGAGAGGAGT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…STAT4 SNPs (rs7574865, rs7582694) were determined by the polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) method [22], [23]. The primers used for the PCR reaction were rs7574865, F:5′-AAAGAAGTGGGATAAAAAGAAGTTTG-3′, R:5′-CCACTGAAATAAGATAACCACTGT-3′, and rs7582694, F:5′-ATCCAACTCTTCTCAGCCCTT-3′, R:5′-TCATAATCAGGAGAGAGGAGT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Its expression may be related to the differentiation of immune cells to inflammatory subsets, production of inflammatory cytokines and autoantibodies, prevention of apoptosis and presentation of autoantigens, which may stimulate the development of autoimmune diseases [155]. STAT4 gene lies adjacent to STAT1 at chromosome 2 (2q32.2–2q32.3).…”
Section: Stat4mentioning
confidence: 99%
“…In this study STAT4 rs7582694 intronic substitution was shown to be significantly increase the risk of SLE occurrence in the sample population. studies carried out by Piotrowski et al [4]. demonstrated a statistically significant contribution of STAT4 (rs7582694) to SLE incidence in polish.Luan et al [15] demonstrated a statistically significant contribution of STAT4 (rs7582694) to SLE incidence in the Mainland Chinese female population.…”
Section: Results:-mentioning
confidence: 93%
“…The role of STAT4 (rs7582694) as a risk allele in development of renal and neurologic manifestation has not established in this study in concordance withLuan et al [15] that reported no association between rs7582694 and sub phenotype of SLE in Chinese Han population.On the other hand, Piotrowski et al [4] found that this SNP can be associated with renal and neurological symptoms of SLE. Since this autoimmune disease is vastly heterogeneous, further studies of this polymorphism's effects on clinical manifestationsof SLE in other populations would be valuable.…”
Section: Results:-mentioning
confidence: 99%
See 1 more Smart Citation